Inovasi Pembelajaran Berbasis Proyek Untuk Meningkatkan Kecerdasan Kognitif Anak Usia 5 – 6 Tahun di TK Islam Amar Ma’ruf - Khotimah, Khusnul; Nisa, Shifa Choerun; Imamah, Imamah (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This study aims to explore the impact of implementing project-based learning on the cognitive intelligence of children aged 5-6 years at Amar Ma'ruf Islamic Kindergarten. Project-based learning is applied through a constructivist model, allowing children to actively engage and build their own understanding through direct experiences. The research employs a qualitative approach with a case study design, gathering in-depth data through continuous observations, interviews with teachers and parents, and documentation of children's project activities. The results reveal that children involved in project-based learning show significant improvement in critical thinking skills, creativity, and social abilities, including collaboration and communication. For instance, in a project themed "Surrounding Environment," children learned to identify environmental issues and created innovative solutions through recycling activities. The findings also indicate that children are more enthusiastic, actively engaged in the learning process, and demonstrate increased self-confidence. Thus, project-based learning not only enhances cognitive intelligence but also supports the development of adaptive and proactive character traits in children. This study recommends the continuous implementation of project-based learning in early childhood education institutions to foster a holistic learning environment that supports comprehensive development. Ongoing support from schools and parents is also crucial for the successful application of this method.